A New Model for Competitive Knowledge Diffusion in Organization Based on the Statistical Thermodynamics - Ju-Yong Jong; Wei-Wei Wu; Sung-Ryol So (Advances in Mathematical Physics)
In this study, we have constructed a new model for competitive knowledge diffusion in organization based on the statistical thermodynamics of physics. In order to achieve the purpose of research, we newly define the absorptive capacity coefficient, the creativity ability coefficient, the depreciation coefficient of knowledge, the ambiguity coefficient of knowledge, and the knowledge affinity coefficient of organizational culture. And various knowledge quantities such as knowledge energy, knowledge temperature, and diffusion coefficient for the knowledge diffusion equation were defined and simulations were carried out by the lattice kinetic method. And, based on the new model, we have successfully studied the impact of the characteristics of members, knowledge itself, and organizational culture on the diffusion of competitive knowledge. The results show that the diffusion velocity of knowledge in the organization increases as the knowledge absorbing ability of the members is larger, and the ambiguity of knowledge has a negative impact on the diffusion of knowledge. The degree of knowledge affinity of organizational culture is a decisive factor in the diffusion and accumulation of knowledge in the organization, and the cultural characteristics of the organization have a much greater influence on the diffusion of competitive knowledge than the personal characteristics of members. Therefore, the organization manager needs to pay more attention to building a better organizational culture than improving personal characteristics. Our research is helpful in analyzing the factors affecting competitive knowledge diffusion and constructing an effective knowledge management system.